Sistem Pendeteksi Panas Kabel dan Peringatan Dini Pada Panel Surya Listrik Menggunakan Sensor Suhu - Ariq Muntasir Adha; Ahmad Yanie; Fajar Dwi Wiliyanto (Universitas Harapan Medan, 2022)
Melting cable skin will short circuit current and cause fire. The factor that makes fires due to short circuits is that they are difficult to detect from the start. The purpose of this research is to design a protection and early warning system for electrical panels. The design method uses AVR ATmega 8 and also uses a C language program for system design. The result of this research is a thermal protection system on the conductor cable which is designed with an electronic circuit and is equipped with a thermal sensor, microcontroller, protection relay and display. Constant Value is 100 C/Volt. The LM 35 sensor converts temperature to voltage with a resolution of 10 mV / °C. With a thermal protection system on the cable, cable damage can be avoided and can also avoid fatal consequences such as melting cables and short circuits that can cause fires.